this is given m(t) = (1/3) + (2/3)e^t m (t) = (.25 + .75e^t)^12 How do these become pmf's and also what is the first and second derivative of the first one. Is it just 2/3 e^t?
Follow Math Help Forum on Facebook and Google+
Originally Posted by wolverine21 this is given m(t) = (1/3) + (2/3)e^t m (t) = (.25 + .75e^t)^12 How do these become pmf's and also what is the first and second derivative of the first one. Is it just 2/3 e^t? Mr F says: Yes. Ah yes. The recognition problem. Big hint: If X ~ Binomial(n, p) then $\displaystyle m_X (t) = [(1 - p) + p e^t]^n$
View Tag Cloud